In-vitro efficacy of six fungicides for the control of Pestalotiopsis sp. associated with taiwanese guava (Psidium guajava L.) cv. Tai-kuo-bar in Paquera, Costa Rica - Serrano, Mauricio (2026)
Introduction. The production of Taiwanese guava in Paquera is constrained by the fungus Pestalotiopsis sp., which causes fruit lesions that reduce quality. Although fungicides are applied for disease management, information on their efficacy remains limited. Objective. To evaluate the in-vitro efficacy of fungicides against Pestalotiopsis sp. associated with Taiwanese guava (Psidium guajava L.) cv. Tai-kuo-bar in the district of Paquera, Puntarenas. Materials and methods. Symptomatic fruits were collected, and fungal isolates were obtained on culture medium and identified morphologically at the genus level. ITS gene sequences were generated and compared against the NCBI (National Center for Biotechnology Information) database. In-vitro efficacy was assessed by inoculating the fungus onto potato dextrose agar (PDA) plates amended with fungicides at commercial dose, 50%, and 10% of the commercial dose. The percentage reduction in mycelial growth relative to the untreated control was calculated. Results and discussion. Pestalotiopsis sp. was confirmed to be associated with fruit lesions. ITS region sequences showed 100% identity with Neopestalotiopsis saprophytica, N. foedans, N. clavispora, and Pestalotiopsis versicolor from the NCBI database. Mycelial growth inhibition was greater than 90% when azoxystrobin, propineb, prochloraz, and difenoconazole were used at the commercial dose. In contrast, copper sulfate pentahydrate and carbendazim showed inhibition of 76.1% and 12.6%, respectively. Conclusions. Azoxystrobin, propineb, prochloraz, and difenoconazole demonstrated high potential for chemical control of Pestalotiopsis. The low efficacy of carbendazim suggests possible resistance in some isolates. Further studies are required to clarify the diversity of Pestalotiopsis species in the region.